Decoction of Cocos nucifera Linn. : Antioxidant Activity, Total Phenolics, and Flavonoids Contents - Taslim, Tuty; Selonni, Fita; Verawaty, Verawaty; Dewi, Irene Puspa; Salim, Reny (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Young coconut husk is one of the wastes that can be processed as a source of herbal medicine. Previous research on young coconut husk has provided information about its tannin content, antioxidant activity, and other bioactivities. This study aims to measure antioxidant activity and total phenolic and flavonoid contents from young coconut husk decoction. The determination of antioxidant activity and total phenolic and flavonoid contents used successively were DPPH, Folin-Ciocalteu, and aluminium chloride methods. The antioxidant activity test of young coconut husk decoction revealed an IC50 value of 47.69 µg/mL. The analysis of total phenolic and flavonoid content in the decoction showed 46,43 mg GAE/gram of husk powder and 4.04 mg RE/gram of husk powder, respectively. Collectively, young coconut husk extracted by decoction has strong antioxidant activity and can be used as a source of phenolics and flavonoids.